THE ACCOUNTING EXCHANGE. - Medsker, Leland L. (The Accounting Review, 1940)
The general use of a C.P.A. certificate as a means of measurement or recognition of an accountant's ability has become so widespread, and the certificate so coveted on the part of most accountants that it would seem as if all who are interested in the profession should be aware of the requirements for the certificate in the various states. In fact, knowledge of the accounting law and of the regulations imposed by the administrative board in each state is probably the first requirement of any potential applicant. The most uniform provisions in all states relate to the candidate's citizenship, his moral character, the examination and the granting of reciprocal certificates. All states require an applicant to be citizen of the United States or to have declared his intention of becoming naturalized. All states require a candidate to be of good moral character. The applicant is usually required to furnish three or more affidavits or references to indicate this quality. The most variable requirement of all is that of professional experience. This article is of help in visualizing the most common requirements.